Is School Adjustment Related to Environmental Empathy and Connectedness to Nature? - Daniel Musitu-Ferrer (Psychosocial Intervention, 2019)
Environmental empathy and connectedness to nature are two main constructs that explain variations in pro-environmental behavior. However, little is known about whether environmental (cognitive and emotional) empathy and connectedness to nature might vary as a function of school adjustment. Participants were 881 Spanish adolescents from 12 to 17 years old (47.2% males). The design was a 2 2 MANOVA (school adjustment sex). Results of the CFA analysis confirmed the theoretical assumptions about two different but related aspects of environmental empathy (cognitive and emotional) and connectedness to nature as a unidimensional construct. Overall, results showed that high school adjustment was related to higher environmental empathy (cognitive and emotional) and greater connectedness to nature. Moreover, interactions were found between school adjustment and sex. Females reported the highest levels of environmental emotional empathy and connectedness to nature (regardless of their school adjustment). By contrast, males with both low and high school adjustment reported lower environmental emotional empathy than females with high school adjustment. Furthermore, only males with high school adjustment reported similar connectedness to nature to that of females (regardless of their school adjustment). Implications of these findings for research and psychosocial interventions in environmental education are discussed.